2017
DOI: 10.1111/febs.14026
|View full text |Cite
|
Sign up to set email alerts
|

Regulating the balance between the kynurenine and serotonin pathways of tryptophan metabolism

Abstract: Tryptophan is metabolized along the kynurenine and serotonin pathways, resulting in formation of kynurenine metabolites, neuroactive serotonin and melatonin. Each pathway is critical for maintaining healthy homeostasis. However, the two pathways are extremely unequal in their ability to degrade tryptophan, and little is known about the mechanisms maintaining the balance between them. Here, we demonstrated that in PC12 cells, a change of expression of key genes of one pathway resulted in a change of expression … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
55
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 73 publications
(58 citation statements)
references
References 83 publications
(123 reference statements)
3
55
0
Order By: Relevance
“…This may also imply decreased melatonin levels which are associated with circadian malfunctioning and can increase the risk of mood disorders (Quera-Salva et al, 2011). Interestingly, melatonin appears to promote the expression of IDO, suggesting a negative feedback loop through which melatonin regulates the balance between kynurenine and 5-HT pathways (Li et al, 2017).…”
Section: Tryptophan Metabolitesmentioning
confidence: 99%
“…This may also imply decreased melatonin levels which are associated with circadian malfunctioning and can increase the risk of mood disorders (Quera-Salva et al, 2011). Interestingly, melatonin appears to promote the expression of IDO, suggesting a negative feedback loop through which melatonin regulates the balance between kynurenine and 5-HT pathways (Li et al, 2017).…”
Section: Tryptophan Metabolitesmentioning
confidence: 99%
“…It plays an important role in tryptophan metabolism by affecting both key enzymes of the two pathways. In particular, it has been demonstrated that melatonin treatment induces the expression of indole-2,3-dioxygenase 1 (IDO1) and enhances the activity of the IDO1 promoter while decreasing the expression of arylalkyl amine N-acetyl-transaminase (AANAT), the enzyme responsible for 5-HT catabolism [ 140 ].…”
Section: The Kynurenines Pathwaymentioning
confidence: 99%
“…Serotonin [5-hydroxytryptamine (5-HT)] synthesis is one of the most important Trp pathways(107). Note that 3% of dietary Trp is used for 5-HT synthesis throughout the body, while only 1% of dietary Trp is used for 5-HT synthesis in the brain(108), where Trp is primarily involved in melatonin synthesis(Figure 2)(109).…”
mentioning
confidence: 99%